A correlative study of autonomic neuropathy and gall bladder volume in patients with diabetes mellitus - Kotresh Doddamane; Adarsh V B; Deepak Kumar V (International Journal of Medical Research and Review, 2016)
Introduction: Diabetic autonomic neuropathy (DAN) is among the least recognized and understood complication of diabetes despite its significant negative impact on survival and quality of life in people with diabetes. Various studies showed that there is increased prevalence of gall bladder diseases like gall stones in patients with diabetes.Methods: This study was done to evaluate gall bladder volume in diabetics, it’s comparison with a control group, and correlation of gallbladder volume in diabetics with various parameters like autonomic neuropathy, age, sex, body mass index, hyperlipidaemia and duration of diabetes. 100 proven diabetic patients and 100 healthy controls were recruited for the study. A detailed history and physical examination findings were recorded. Autonomic neuropathy was determined by using simple noninvasive bedside tests. Fasting gallbladder volume was calculated using ellipsoid formula by ultrasonography.Results: The mean fasting gallbladder volume in diabetics was 23.1±7.3 ml as compared to controls i.e 13.0±3.4ml.Conclusion: When type 2 diabetics were sub grouped according to the presence of autonomic neuropathy, higher gallbladder volumes were seen in patients with autonomic neuropathy.